Short‐term tamoxifen treatment has long‐term effects on metabolism in high‐fat diet‐fed mice with involvement of Nmnat2 in POMC neurons. Issue 19 (19th September 2018) - Liu, Zhiyuan; Cheng, Yalan; Luan, Yi; Zhong, Wuling; Lai, Hejin; Wang, Hui; Yu, Huimin; Yang, Yale; Feng, Ning; Yuan, Feixiang; Huang, Rui; He, Zhishui; et al.
Abstract : Short‐term tamoxifen treatment has effects on lipid and glucose metabolism in mice fed chow. However, its effects on metabolism in mice fed high‐fat diet (HFD) and the underlying mechanisms are unclear. Here, we show that tamoxifen treatment for 5 days decreases fat mass for as long as 18 weeks in mice fed HFD. Tamoxifen alters mRNA levels of some genes involved in lipid metabolism in white adipose tissue and improves glucose and insulin tolerance as well as hepatic insulin signaling for 12–20 weeks. Proopiomelanocortin (POMC) neuron‐specific deletion of nicotinamide mononucleotide adenylyltransferase 2 (Nmnat2) attenuates the effects of tamoxifen on glucose and insulin tolerance. These data demonstrate that short‐term injection of tamoxifen has long‐term effects on lipid and glucose metabolism in HFD mice with involvement of Nmnat2 in POMC neurons. Abstract :